Monitoring the impact of global warming on wheat cultivation in the Mughan Plain (Germi) Using the atmospheric circulation model - bromand Salahi; vahid safarian zangir (تحقیقات کاربردی علوم جغرافیایی)
Global warming and temperature rise will have many effects on different sectors, including agriculture, the warming of the earth will increase the rate of evaporation, and consequently the increase in the demand for agricultural products will increase. In this study, in order to monitor the effect of global warming on Mughan Plain wheat, using the LARS-WG model as a relatively inexpensive and accurate instrument for producing climate multi-yearly climate change scenarios On a daily basis, In Ardabil province, Germi Station was selected as the representative of the three stations in the study area due to the data in the appropriate statistical period. In the present study, to monitor the effect of global warming on precipitation fluctuations, as well as in the production and cultivation of wheat crop in Moghan plain, the LARS-WG model and the HADCM3 climate model output under A1B scenario as well as climate data (minimum temperature, maximum temperature, precipitation and Daily Sunshine) The Germys station was used over a 14 year period (2004-2007).The results of the research show that by comparing the monthly mean of these parameters, this result was obtained that at confidence level 1 there is not a significant difference between the simulation data from the model and observational data in the base period and the mean The climatic parameters of the data obtained from the model and the actual data are similar and there is a high correlation between them. Finally, by comparing observational monthly meanings and modeling of climatic elements of precipitation, minimum and maximum temperatures and sunshine were shown using statistical parameters RMSE, MAE, NA and R2 The model (LARS-WG5) is used to accurately simulate daily data in the parameters of the Mughan Plain, Ardebil province. The results of this study showed that the average decrease in yield of irrigated wheat and the decrease of its production in the study area could be due to the decrease of precipitation and the increase of the regional temperature which is due to global warming.